Economic Interdependence and War in Ukraine: The Role of Economic Interdependence in the War’s Origin (Global Journal of Human-Social Science, 2024)
Lenin is said to have explained his political tactics with the metaphor of a soldier stabbing a target with a bayonet if the bayonet hits something solid the soldier should retreat but if it penetrates the target he should keep stabbing That anecdote is relevant now because there is an explanation for Russia s decision to invade Ukraine that appeals to the same reasoning incidentally until 1991 Putin was an active member of the party founded by Lenin Specifically it is an explanation of why the Russian government may have underestimated the magnitude of the sanctions that would be imposed against that country if it invaded Ukraine We know the Russian government underestimated those sanctions because of information such as the following before the invasion Russia had international reserves equivalent to some US 650 billion of which some US 300 billion were deposited in financial entities of Western powers 1 That is Russia had deposited around half its international reserves in financial entities that confiscated them after the invasion of Ukraine when sanctions were applied If it had foreseen that possibility the Russian government would have put its reserves in a safe place before launching the invasion